2019
DOI: 10.20546/ijcmas.2019.809.269
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of Dual Colour Tinting Technology in Gerbera and Carnation

Abstract: Karnataka to standardize the dual colour tinting technology in gerbera and carnation by using 6 different food dyes combinations (Red and Yellow, Orange and Green, Yellow and Pink, Red and Green, Blue and Green, Orange and Yellow) along with control at five per cent concentration along with three different immersion time (7.5, 10 and 12.5 hrs). The tinted flowers were evaluated for colour intensity, vase life, volume of water uptake and relative water content (RWC).The results showed that the control flowers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Although not significantly different from other treatments, the control did not have a rating of 3 points until day 11. Previous studies also reported that use of dyes on cut rose (Rosa hybrida L.), gerbera (Gerbera jamesonii L.), carnation, and gladiolus (Gladiolus communis L.) stems has shown a 1-to 3-d shorter vase life than the control (Shim et al, 2012;Sneha et al, 2019). The possible reason for this could be that use of spray paint or highlighter strongly affected the antioxidant defense system and resulted in decreased vase life (Aalifar et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although not significantly different from other treatments, the control did not have a rating of 3 points until day 11. Previous studies also reported that use of dyes on cut rose (Rosa hybrida L.), gerbera (Gerbera jamesonii L.), carnation, and gladiolus (Gladiolus communis L.) stems has shown a 1-to 3-d shorter vase life than the control (Shim et al, 2012;Sneha et al, 2019). The possible reason for this could be that use of spray paint or highlighter strongly affected the antioxidant defense system and resulted in decreased vase life (Aalifar et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, the results from our current study show that the use of highlighter solution alone does not appear to be as toxic to the flowers as the paint, at least at lower rates, as the highlighter solution was left in the vase water for the duration of the experiment and no differences were seen among controls for vase life. Sneha et al (2019) examined six different food dyes on cut gerbera, carnation, and gladiolus stems and reported that a longer soak time (7.5 h) resulted in brighter flowers but reduced vase life.…”
Section: Discussionmentioning
confidence: 99%